Օտար յատուկ անունների տառադարձութեան սկզբունքները․ Մասն ԺԱ. - վրացերէն - Միքայէլեան, Արմէն (տպ. Atlas)
The article is the last in the series that deals with the transliteration (transcription) of foreign proper names into Armenian (the way to transcribe foreign names in Armenian characters). The references of the previous articles are: 1) The Principles of Transliterating Foreign Proper Names into Armenian, Part I - Middle Eastern Languages [in Armenian], Haigazian Armenological Review, 40:2020, pp. 341-64.2) The Principles of Transliterating Foreign Proper Names into Armenian, Part II - Classical Languages (Ancient Greek and Latin) [in Armenian], Bazmavep, CLXXVIllfl- 2):2020, pp. 304-36. 3) The Principles of Transliterating Foreign Proper Names into Armenian, Part III - French Language [in Armenian], Haigazian Armenological Review, 41:2021, pp. 44366. 4) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part IV - English Language [in Armenian], Handes Amsorya, CXXXV:2021, pp. 197-246. 5) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, PartV - German Language [in Armenian], Bazmavep, CLXXX(1-2):2022, pp. 277-303. 6) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part VI - Italian and Spanish Languages [in Armenian], Bazmavep, CLXXX (3-4):2022, pp. 271-300. 7) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part VII - Russian (Compared to Other Slav(on)ic Languages) [in Armenian], Haigazian Armenological Review, 42/2:2022, pp. 169-98. 8) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part VIII - Chinese Language [in Armenian], Bazmavep, CLXXXI(1-2):2023, pp. 272-305. 9) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part IX - Japanese Language [in Armenian], Haigazian Armenological Review, 44/1:2024, pp. 85-106. 10) The Principles of Transliterating (Transcribing) Foreign Proper Names into Armenian, Part X - Hindi Language and the Indian Sub-Continent [in Armenian], Bazmavep, CLXXXII(1-2):2024, pp. 361-405.
Keywords: Հայ լեզուաբանութիւն; Տառադարձութիւն